An energy efficient teaching learning based optimization approach for common content distribution in mobile ad hoc networks. (November 2018) - Maiti, Mahendra; Mukherjee, Srijit; Thakurta, Parag Kumar Guha
Abstract: An energy efficient content distribution technique in mobile ad hoc networks is proposed in this paper. Based on bit rate, remaining energy and maximum allowable delay, a fitness value is evaluated for each node in the network. A set of nodes having maximum fitness values are elected as cluster heads. It is determined by applying teaching learning based optimization technique, only after the nodes satisfy an energy constraint. The clusters of nodes are formed by assigning the remaining nodes to their corresponding cluster heads. The cluster heads can receive the required packets from the base station via long range communication and forward the same to the cluster members. Efficient energy expenditure by this approach leads to an increased network lifetime. The experimental results show effectiveness of the proposed approach over K-means Clustering and U+M techniques in terms of reduced energy consumption and improved network lifetime.